Balance the electrical properties and mechanical properties of carbon black filled immiscible polymer blends with a double percolation structure. (1st March 2017) - Chen, Jianwen; Cui, Xihua; Sui, Kunyan; Zhu, Yutian; Jiang, Wei
Abstract: It has been widely reported that construction of a double percolation structure in the conductive polymer composites (CPCs) can effectively reduce the percolation thresholds of the composites. However, the mechanical properties of these types of CPCs are normally inferior because of the weak interfacial interactions between the immiscible polymer blends. In the current study, we constructed a perfect double percolation structure in the CB/PS/PP composites at PS/PP weight ratio of 60w/40w to reduce the percolation threshold and introduced the fourth component, i.e. styrene–ethylene/butylene–styrene (SEBS) triblock copolymer, as the compatibilizer to improve the mechanical properties. Although the mechanical properties are significantly improved after the addition of SEBS, the electrical conductivity shows a remarkable decline when SEBS content is higher than 3 wt%. This is because that the addition of compatibilizer into a co-continuous immiscible polymer blend will reduce the sizes of the phase domains, thereby causing a damage of phase continuity of the double percolation structure. However, it is found that the electrical properties can be still superior because of the maintaining of the double percolation structure and the mechanical properties can also be significantly improved when SEBS content is 2 wt%, which can well balance the electrical properties and mechanical properties of the CPCs containing a double percolation structure.